Analysis of Plasmalogen Species in Foodstuffs. Issue 2 (5th January 2016) - Yamashita, Shinji; Kanno, Susumu; Honjo, Ayako; Otoki, Yurika; Nakagawa, Kiyotaka; Kinoshita, Mikio; Miyazawa, Teruo
Abstract: Ethanolamine plasmalogen (PlsEtn), which is present at high levels in brains, is believed to be involved in neuronal protection. The present study was performed to search for PlsEtn resources in foodstuffs. The foodstuffs examined showed a wide range of PlsEtn contents from 5 to 549 μmol/100 g wet wt. The marine invertebrates, blue mussel, and ascidian had high PlsEtn contents (over 200 μmol/100 g wet wt). Profiling of the molecular species showed that the predominant fatty acids of PlsEtn species were 20:5 (EPA) and 22:6 (DHA) at the sn ‐2 position of the glycerol moiety in marine foodstuffs, whereas major PlsEtn species in land foodstuffs were 20:4. Following quantitative analysis by multiple reaction monitoring, the ascidian viscera were shown to contain the highest levels of 18:0/20:5‐PlsEtn and 18:0/22:6‐PlsEtn (86 and 68 μmol/100 g wet wt, respectively). In order to evaluate a neuronal antiapoptotic effect of these PlsEtn species, human neuroblastoma SH‐SY5Y cells were treated with ethanolamine glycerophospholipid (EtnGpl), purified from the ascidian viscera, under serum starvation conditions. Extrinsic EtnGpl from ascidian viscera showed stronger suppression of cell death induced by serum starvation than with bovine brain EtnGpl. The EtnGpl from ascidian viscera strongly suppressed the activation of caspase 3. These results suggest that PlsEtn, especially that containing EPA and DHA, from marine foodstuffs is potentially useful for a therapeutic dietary supplement preventing neurodegenerative diseases, such as Alzheimer's disease (AD).